Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Get detailed and accurate answers to your questions from a community of experts on our comprehensive Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Let's break the problem into parts and solve it step-by-step.
### Part 1: Show that [tex]\(\frac{1}{z} = \frac{\bar{z}}{|z|^2}\)[/tex]
Let [tex]\( z = a + bi \)[/tex] be a complex number where [tex]\(a\)[/tex] and [tex]\(b\)[/tex] are real numbers and [tex]\(i\)[/tex] is the imaginary unit.
1. Complex Conjugate:
The complex conjugate of [tex]\( z \)[/tex], denoted by [tex]\(\bar{z}\)[/tex], is:
[tex]\[ \bar{z} = a - bi \][/tex]
2. Magnitude of z:
The magnitude (or modulus) of [tex]\(z\)[/tex], denoted by [tex]\(|z|\)[/tex], is:
[tex]\[ |z| = \sqrt{a^2 + b^2} \][/tex]
Thus, the square of the magnitude is:
[tex]\[ |z|^2 = a^2 + b^2 \][/tex]
3. Reciprocal of z:
We need to find the reciprocal of [tex]\(z\)[/tex], which is [tex]\(\frac{1}{z}\)[/tex].
Recall the property of complex numbers that [tex]\(\frac{1}{z}\)[/tex] can be expressed using its conjugate and magnitude:
[tex]\[ \frac{1}{z} = \frac{1}{a+bi} \][/tex]
To simplify, multiply the numerator and the denominator by the conjugate of the denominator:
[tex]\[ \frac{1}{a+bi} \cdot \frac{a-bi}{a-bi} = \frac{a - bi}{(a+bi)(a-bi)} = \frac{a - bi}{a^2 + b^2} \][/tex]
Therefore,
[tex]\[ \frac{1}{z} = \frac{a - bi}{a^2 + b^2} = \frac{\bar{z}}{|z|^2} \][/tex]
Thus, we have shown that:
[tex]\[ \frac{1}{z} = \frac{\bar{z}}{|z|^2} \][/tex]
### Part 2: Show that [tex]\(\bar{z} = -z\)[/tex] implies [tex]\(z\)[/tex] has only an imaginary part
Given [tex]\(\bar{z} = -z\)[/tex]:
[tex]\[ a - bi = - (a + bi) \][/tex]
Equating real and imaginary parts, we get:
[tex]\[ a = -a \quad \text{and} \quad -bi = -bi \][/tex]
From [tex]\(a = -a\)[/tex], we get [tex]\( a = 0 \)[/tex]. Thus, [tex]\(z\)[/tex] becomes purely imaginary, [tex]\( z = bi \)[/tex].
### Part 3: Solve for [tex]\(a\)[/tex] and [tex]\(b\)[/tex]
Given the equation:
[tex]\[ z(2 - i) = (\bar{z} + 1)(1 + i) \][/tex]
We need to find [tex]\(a\)[/tex] and [tex]\(b\)[/tex] such that this equation is satisfied.
First, express [tex]\(z\)[/tex] and [tex]\(\bar{z}\)[/tex]:
[tex]\[ z = a + bi \quad \text{and} \quad \bar{z} = a - bi \][/tex]
Substitute these into the given equation:
[tex]\[ (a + bi)(2 - i) = ((a - bi) + 1)(1 + i) \][/tex]
Expand both sides:
1. Left-hand Side:
[tex]\[ (a + bi)(2 - i) = 2a + 2bi - ai - b i^2 = 2a + 2bi - ai + b = (2a + b) + (2b - a)i \][/tex]
2. Right-hand Side:
[tex]\[ ((a - bi) + 1)(1 + i) = (a - bi + 1)(1 + i) = (a + 1 - bi)(1 + i) \][/tex]
Expand:
[tex]\[ (a + 1 - bi)(1 + i) = (a + 1)(1 + i) - bi(1 + i) \][/tex]
[tex]\[ = (a + 1) + (a + 1)i - bi - b i^2 \][/tex]
[tex]\[ = a + 1 + (a + 1)i - bi + b \][/tex]
[tex]\[ = (a + 1 + b) + (a - b + 1)i \][/tex]
Now equate the real and imaginary parts from both sides:
[tex]\[ 2a + b = a + 1 + b \quad \text{(real part)} \][/tex]
[tex]\[ 2b - a = a - b + 1 \quad \text{(imaginary part)} \][/tex]
From the real part equation:
[tex]\[ 2a + b = a + 1 + b \][/tex]
[tex]\[ 2a = a + 1 \][/tex]
[tex]\[ a = 1 \][/tex]
From the imaginary part equation:
[tex]\[ 2b - a = a - b + 1 \][/tex]
[tex]\[ 2b - 1 = 1 - b + 1 \][/tex]
[tex]\[ 2b - 1 = 2 - b \][/tex]
[tex]\[ 3b = 3 \][/tex]
[tex]\[ b = 1 \][/tex]
Thus, the values of [tex]\(a\)[/tex] and [tex]\(b\)[/tex] that satisfy the given equation are:
[tex]\[ a = 1, \quad b = 1 \][/tex]
Hence [tex]\( z = 1 + i \)[/tex].
### Part 1: Show that [tex]\(\frac{1}{z} = \frac{\bar{z}}{|z|^2}\)[/tex]
Let [tex]\( z = a + bi \)[/tex] be a complex number where [tex]\(a\)[/tex] and [tex]\(b\)[/tex] are real numbers and [tex]\(i\)[/tex] is the imaginary unit.
1. Complex Conjugate:
The complex conjugate of [tex]\( z \)[/tex], denoted by [tex]\(\bar{z}\)[/tex], is:
[tex]\[ \bar{z} = a - bi \][/tex]
2. Magnitude of z:
The magnitude (or modulus) of [tex]\(z\)[/tex], denoted by [tex]\(|z|\)[/tex], is:
[tex]\[ |z| = \sqrt{a^2 + b^2} \][/tex]
Thus, the square of the magnitude is:
[tex]\[ |z|^2 = a^2 + b^2 \][/tex]
3. Reciprocal of z:
We need to find the reciprocal of [tex]\(z\)[/tex], which is [tex]\(\frac{1}{z}\)[/tex].
Recall the property of complex numbers that [tex]\(\frac{1}{z}\)[/tex] can be expressed using its conjugate and magnitude:
[tex]\[ \frac{1}{z} = \frac{1}{a+bi} \][/tex]
To simplify, multiply the numerator and the denominator by the conjugate of the denominator:
[tex]\[ \frac{1}{a+bi} \cdot \frac{a-bi}{a-bi} = \frac{a - bi}{(a+bi)(a-bi)} = \frac{a - bi}{a^2 + b^2} \][/tex]
Therefore,
[tex]\[ \frac{1}{z} = \frac{a - bi}{a^2 + b^2} = \frac{\bar{z}}{|z|^2} \][/tex]
Thus, we have shown that:
[tex]\[ \frac{1}{z} = \frac{\bar{z}}{|z|^2} \][/tex]
### Part 2: Show that [tex]\(\bar{z} = -z\)[/tex] implies [tex]\(z\)[/tex] has only an imaginary part
Given [tex]\(\bar{z} = -z\)[/tex]:
[tex]\[ a - bi = - (a + bi) \][/tex]
Equating real and imaginary parts, we get:
[tex]\[ a = -a \quad \text{and} \quad -bi = -bi \][/tex]
From [tex]\(a = -a\)[/tex], we get [tex]\( a = 0 \)[/tex]. Thus, [tex]\(z\)[/tex] becomes purely imaginary, [tex]\( z = bi \)[/tex].
### Part 3: Solve for [tex]\(a\)[/tex] and [tex]\(b\)[/tex]
Given the equation:
[tex]\[ z(2 - i) = (\bar{z} + 1)(1 + i) \][/tex]
We need to find [tex]\(a\)[/tex] and [tex]\(b\)[/tex] such that this equation is satisfied.
First, express [tex]\(z\)[/tex] and [tex]\(\bar{z}\)[/tex]:
[tex]\[ z = a + bi \quad \text{and} \quad \bar{z} = a - bi \][/tex]
Substitute these into the given equation:
[tex]\[ (a + bi)(2 - i) = ((a - bi) + 1)(1 + i) \][/tex]
Expand both sides:
1. Left-hand Side:
[tex]\[ (a + bi)(2 - i) = 2a + 2bi - ai - b i^2 = 2a + 2bi - ai + b = (2a + b) + (2b - a)i \][/tex]
2. Right-hand Side:
[tex]\[ ((a - bi) + 1)(1 + i) = (a - bi + 1)(1 + i) = (a + 1 - bi)(1 + i) \][/tex]
Expand:
[tex]\[ (a + 1 - bi)(1 + i) = (a + 1)(1 + i) - bi(1 + i) \][/tex]
[tex]\[ = (a + 1) + (a + 1)i - bi - b i^2 \][/tex]
[tex]\[ = a + 1 + (a + 1)i - bi + b \][/tex]
[tex]\[ = (a + 1 + b) + (a - b + 1)i \][/tex]
Now equate the real and imaginary parts from both sides:
[tex]\[ 2a + b = a + 1 + b \quad \text{(real part)} \][/tex]
[tex]\[ 2b - a = a - b + 1 \quad \text{(imaginary part)} \][/tex]
From the real part equation:
[tex]\[ 2a + b = a + 1 + b \][/tex]
[tex]\[ 2a = a + 1 \][/tex]
[tex]\[ a = 1 \][/tex]
From the imaginary part equation:
[tex]\[ 2b - a = a - b + 1 \][/tex]
[tex]\[ 2b - 1 = 1 - b + 1 \][/tex]
[tex]\[ 2b - 1 = 2 - b \][/tex]
[tex]\[ 3b = 3 \][/tex]
[tex]\[ b = 1 \][/tex]
Thus, the values of [tex]\(a\)[/tex] and [tex]\(b\)[/tex] that satisfy the given equation are:
[tex]\[ a = 1, \quad b = 1 \][/tex]
Hence [tex]\( z = 1 + i \)[/tex].
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.